Encyclopedia of New Jersey - Lurie, Maxine N., 1940-; Mappen, Marc. (New Brunswick, N.J. : Rutgers University Press, 2004)
Contains nearly original articles, along with illustrations and maps, collecting a wealth of information about the state of New Jersey.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: New Jersey -- Encyclopedias; New Jersey -- Encyclopédies.; HISTORY -- State & Local; HISTORY -- State & Local -- General; New Jersey; Electronic books; Encyclopedia; encyclopedias; Encyclopedias; Encyclopedias; Encyclopédies.